Characterization and application of size-sorted zonal chondrocytes for articular cartilage regeneration. (May 2018) - Yin, Lu; Wu, Yingnan; Yang, Zheng; Denslin, Vinitha; Ren, Xiafei; Tee, Ching Ann; Lai, Zhangxing; Lim, Chwee Teck; Han, Jongyoon; Lee, Eng Hin
Abstract: Current clinical approaches for articular cartilage repair have not been able to restore the tissue with zonal architecture, and its biomechanical and functional properties. Mimicking the zonal organization of articular cartilage in neo-tissue by implanting zonal chondrocyte subpopulations in multilayer construct could enhance the functionality of the graft, engineering of stratified tissue has not yet been realized due to lack of efficient and specific zonal chondrocyte isolation protocol. We show that by using a spiral microchannel device, the superficial, middle and deep zone chondrocytes can be separated based on cell size, and enriched from full thickness porcine cartilage in a high-throughput, label-free manner. The size-sorted cells show zone-specific characteristics in RT-PCR analysis of zonal cartilage markers. Both freshly sorted and two-passage expanded zonal chondrocytes formed cartilage tissue in 3D hydrogel, bearing respective zonal characteristics, indicated by RT-PCR, histology, extracellular matrix proteins, and mechanical compression test. In the proof-of-concept in vivo study using a rodent cartilage defect model, the size-sorted zonal chondrocytes when delivered in bi-layered hydrogel construct, facilitated better cartilage repair with mechanically enhanced cartilage tissue, in comparison to conventional chondrocytes implantation. This study provides an effective approach to obtain large numbers of zonal chondrocytes, and demonstrates the translational potential of stratified zonal chondrocyte implantation for clinical repair of critical size cartilage defects.